The Aqueous Calyx Extract of Hibiscus sabdariffa Lowers Blood Pressure and Heart Rate via Sympathetic Nervous System Dependent Mechanisms (Nigerian Journal of Physiological Sciences, 2021)
Summary: The antihypertensive effect of Hibiscus sabdariffa (HS) has been validated in animals and man. This study tested the hypothesis that its hypotensive effect may be sympathetically mediated. The cold pressor test (CPT) and handgrip exercise (HGE) were performed in 20 healthy subjects before and after the oral administration of 15mg/Kg HS. The blood pressure (BP) and heart rate (HR) responses were measured digitally. Mean arterial pressure (MAP; taken as representative BP) was calculated. Results are expressed as mean ±SEM. P